Digest - Herfarth, Christian; Lehnert, Thomas (The British journal of surgery, 1994)
This month's selection from the October to December 1993 issues of Der Chirurg is written by Professor Christian Herfarth and Dr Thomas Lehnert. A digest of the BJS for the same period, written by Professor John Farndon, appears in the April 1994 issue of the German journal.